Conservation and management prospects of the Persian and Malayan leopards. - Hussin, Mohamed Zakaria; Sanei, Arezoo (2011)
Persian leopard. Being the largest predator of wide distribution in the mountains of Iran, the Persian leopard (Panthera pardus saxicolor Pocock 1927) is acknowledged as the "King of the Mountains" by local settlers. After the extinction of the Persian lion (Panthera leo) and the Caspian tiger (Panthera tigris), the Persian leopard is the last member of genus Panthera which still remains in its natural habitats in Iran. About five decades ago, living in most rural communities of Iran was based on the traditional methods of cultivation and animal husbandry, while urban growth and development were witnessing a slow progress. As a result, in many of the natural habitats in Iran, flocks of wild sheep and wild goat could be observed to occur widely in the dale hills and high mountains, specifically in the long ranges of Zagros and Alborz Mountains. Likewise, signs of the leopard presence could be found frequently in these areas.